2016
DOI: 10.1007/s10518-016-9994-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensity measures that reduce collapse capacity dispersion of P-delta vulnerable simple systems

Abstract: The study evaluates two alternative seismic intensity measures (IMs) that reduce the collapse capacity dispersion of inelastic non-degrading single-degree-of-freedom (SDOF) systems vulnerable to the P-delta effect. This dispersion of collapse capacity is caused by record-to-record variability, which refers to frequency content variation of the ground motions used in the dynamic analyses. This reduction (of dispersion) is achieved utilizing efficient elastic pseudo-spectral acceleration based IMs. The first set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…The resulting period intervals DT are S a;gm ðT 1 ; 1:6T 1 Þ, S a;gm ðT 1 ; 2:0T 1 Þ, and S a;gm ðT 1 ; 1:3T 1 Þ. Tsantaki et al (2017) found that the period interval from T ð1Þ ¼ T 1 to T ðnÞ ¼ 1:6T 1 leads on average to the smallest collapse capacity dispersion of P-delta vulnerable SDOF systems.…”
Section: Intensity Measures Covering the Effect Of Period Elongationmentioning
confidence: 95%
See 3 more Smart Citations
“…The resulting period intervals DT are S a;gm ðT 1 ; 1:6T 1 Þ, S a;gm ðT 1 ; 2:0T 1 Þ, and S a;gm ðT 1 ; 1:3T 1 Þ. Tsantaki et al (2017) found that the period interval from T ð1Þ ¼ T 1 to T ðnÞ ¼ 1:6T 1 leads on average to the smallest collapse capacity dispersion of P-delta vulnerable SDOF systems.…”
Section: Intensity Measures Covering the Effect Of Period Elongationmentioning
confidence: 95%
“…They found that the optimal parameters depend strongly on the actual deformation of the structure, i.e., elastic, moderately inelastic, or at onset of collapse. Bianchini et al (2009) Bianchini et al (2009), where S a is discretized at 10 log-spaced periods within DT, Tsantaki et al (2017) discretized S a at equally spaced periods T ðiÞ within DT (Fig. 1d),…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering appropriate seismic intensity measure (IM) is important for nonlinear dynamic analyses. Tsantaki et al [9] proposed two IMs to reduce the collapse capacity dispersion of SDOF systems that are vulnerable to the P-Delta effect. The collapse capacity dispersion is caused by the ground motion variability and the variations of frequency content of ground motions.…”
Section: Introductionmentioning
confidence: 99%